CABARAN SEMASA TULISAN JAWI SEBAGAI WARISAN MASYARAKAT PERADABAN BANGSA MELAYU - Ahmad, Shakila; Othman, Hussain; Afkari, Rafiuddin; Rusdi, Mikdar; Abdul Rahim, Mohd. Hisyam (Journal of Techno-Social, 2012)
Islam has come to bring together the Malay Jawi script which has served as a means of dissemination of knowledge, especially knowledge of religion among the Malay community. Islam became a legacy to the Malays so that they are included in the definition of the Malays as contained in Article 160 (2) of the Constitution, namely the Muslim, practicing traditional Malay culture and speak the language. However Jawi script which brought together the arrival of Islam had a different fate for his role has been taken over by Rumi. Even the position of Jawi today's increasingly marginalized and no longer seen as a symbol of Malay civilization as it was impassable in the golden age of Malay civilization ago. Hence this paper discusses some of the challenges faced by Jawi nowadays that need to be addressed to ensure the Jawi script may continue to be upheld its use in accordance with its position as a civilization heritage of the Malays.